Tahir dalam Al-Qur’an (Analisis Komparatif Tafsir Ruh Al-Ma’any dan Mafatih Al-Ghaib) pada Surat Al-Muddassir dan Al-Hajj - Razhak, Abdul; Norfaridatunnisa, Norfaridatunnisa; Mahfuz, Taufik Warman (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
The purpose of this research is to describe tahir in the Qur'an (comparative analysis of the tafsir of the spirit of al-ma'any and mafatih al-ghaib). The research method used in this study is a literature study with a qualitative approach. The data used in this study is the holy book of the Qur'an, precisely in Surah al-Muddassir and Surah Al-Hajj along with the interpretation of the spirit of al-Ma'any by Mahmud Al-alusi and Mafatih al-Ghaib by Imam Fakhruddin Ar-Razi. The results of this study show that Tafsir Mafatih Al-Ghaib to understand the meaning of purification with various kinds of discussions according to the situation. Meanwhile, the Tafsir Ruh Al-Ma'any emphasizes that the command to purify oneself from reprehensible morals.